2004
DOI: 10.1159/000082201
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Oxidative Stress in Renal Insufficiency

Abstract: Background/Aims: Iron (Fe) can cause tissue injury and oxidative stress by catalyzing hydroxyl radical production and lipid peroxidation. Intravenous (i.v.) Fe preparations are routinely administered to treat anemia in patients with chronic renal failure (CRF), a condition marked by oxidative stress and inflammation. In an earlier study, we showed that iron overload augments oxidative stress in the cardiovascular tissues of CRF rats. This study was designed to expand these observations to other major organs. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…[48] Our results are in agreement with similar studies showing that increased MPO activity plays a role in CRF-induced oxidative injury, and treating the animals with anti-inflammatory or antioxidant agents prevents tissue damage by inhibiting neutrophil infiltration. [49,50] Moreover, the anti-inflammatory effect of E 2 observed in all the CRF-injured tissues appears to include an inhibition on the accumulation of neutrophils and on the generation of superoxide radicals. Similarly, E 2 was shown to inhibit neutrophil infiltration and ICAM-1 expression in endotoxin-induced glomerular inflammatory response.…”
Section: Discussionmentioning
confidence: 97%
“…[48] Our results are in agreement with similar studies showing that increased MPO activity plays a role in CRF-induced oxidative injury, and treating the animals with anti-inflammatory or antioxidant agents prevents tissue damage by inhibiting neutrophil infiltration. [49,50] Moreover, the anti-inflammatory effect of E 2 observed in all the CRF-injured tissues appears to include an inhibition on the accumulation of neutrophils and on the generation of superoxide radicals. Similarly, E 2 was shown to inhibit neutrophil infiltration and ICAM-1 expression in endotoxin-induced glomerular inflammatory response.…”
Section: Discussionmentioning
confidence: 97%
“…21 Although the exact mechanisms of inflammation and oxidative stress have not been accurately elucidated in CKD patients, a number of following described factors appear to be involved, including uremic toxins, 3 rennin-angiotensin system, 22 hypertension, 23 underlying diseases (diabetes, autoimmune diseases, etc. ), 24 infection, iron overload, 25 antioxidant deficiency, 26 etc. Oxidative stress can provoke inflammation via activating NF-kB and consequent generation of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that all three agents resulted in a massive and similar increase in lipid peroxidation. Whole-animal studies show that intravenous administration of iron dextran in rats with chronic renal failure also induces oxidative stress (20,21).…”
Section: Iron Generates Oxidative Stress In Humansmentioning
confidence: 99%